2013
DOI: 10.1016/j.atherosclerosis.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four U.S. populations: The Population Architecture using Genomics and Epidemiology (PAGE) study

Abstract: Background A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. Methods Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…One sufficiently powered population-based study, including 22 513 participants, did observe a positive association between the GCKR minor allele (rs780094) and carotid artery plaques, albeit only in Native Americans [67].…”
Section: Glucokinase Regulatory Protein In Relation To Cardiovascularmentioning
confidence: 98%
“…One sufficiently powered population-based study, including 22 513 participants, did observe a positive association between the GCKR minor allele (rs780094) and carotid artery plaques, albeit only in Native Americans [67].…”
Section: Glucokinase Regulatory Protein In Relation To Cardiovascularmentioning
confidence: 98%
“…We finally included 9 manuscripts, [28][29][30][31][32][33][34][35][36] and the number of Table 4 Age-and Sex-adjusted Analysis Across Genotype Groups participants included in the meta-analysis ranged from 6676 (rs17465637 and rs10455872) to 32056 (rs1333049). The results reported in the studies included in the meta-analysis are shown in Table 3 of the supplementary material.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…Similarities in resting cardiovascular structure and function between Indigenous and European-descendant young adults suggest that subclinical cardiovascular disease development may occur similarly across ethnicities. These similarities in cardiovascular structure and function may seem counterintuitive given the greater experiences of obesity, diabetes and cardiovascular disease among Indigenous populations [2,36]; however, similar or more favourable vascular structure and function have been previously identified among Indigenous populations compared to European descent [3739]. Similarities in cardiovascular structure and function, combined with previous similarities in vascular structure and function [3739], suggest that the differences in cardiovascular disease are rooted outside of cardiovascular physiology and genetics, as previously suggested [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…These similarities in cardiovascular structure and function may seem counterintuitive given the greater experiences of obesity, diabetes and cardiovascular disease among Indigenous populations [2,36]; however, similar or more favourable vascular structure and function have been previously identified among Indigenous populations compared to European descent [3739]. Similarities in cardiovascular structure and function, combined with previous similarities in vascular structure and function [3739], suggest that the differences in cardiovascular disease are rooted outside of cardiovascular physiology and genetics, as previously suggested [40,41]. Alternatively, while ethnic differences in resting cardiovascular dynamics were not identified, ethnic differences may be more apparent when evaluating ECG during maximal or near-maximal exercise stress tests which are prognostic for identifying cardiac arrhythmias and abnormalities among asymptomatic individuals with underlying cardiovascular disease [42].…”
Section: Discussionmentioning
confidence: 99%